M. Pascual Tomas : inter-departmental correspondence - McDonald, Florence
026-0072-001 I.C.3. TRADES UNION CONGRESS INTER-DEPARTMENTAL CORRESPONDENCE. From: F. McDonald To: Mr. Bell. Department: Secretary's Date: 9th June, 1939. SUBJECT. M. Pascual Tomas. Sir Walter would like you to see what you can do with this matter of Mr. Tomas' wife and daughter, and he would like you to draft a letter to him saying that Sir Walter will give all the assistance he can and realises the strain of the present position. 292/946/26/72